Age-related macular degeneration. Issue 10153 (29th September 2018) - Mitchell, Paul; Liew, Gerald; Gopinath, Bamini; Wong, Tien Y
Summary: Age-related macular degeneration is a leading cause of visual impairment and severe vision loss. Clinically, it is classified as early-stage (medium-sized drusen and retinal pigmentary changes) to late-stage (neovascular and atrophic). Age-related macular degeneration is a multifactorial disorder, with dysregulation in the complement, lipid, angiogenic, inflammatory, and extracellular matrix pathways implicated in its pathogenesis. More than 50 genetic susceptibility loci have been identified, of which the most important are in the CFH and ARMS2 genes. The major non-genetic risk factors are smoking and low dietary intake of antioxidants (zinc and carotenoids). Progression from early-stage to late-stage disease can be slowed with high-dose zinc and antioxidant vitamin supplements. Intravitreal anti-vascular endothelial growth factor therapy (eg, ranibizumab, aflibercept, or bevacizumab) is highly effective at treating neovascular age-related macular degeneration, and has markedly decreased the prevalence of visual impairment in populations worldwide. Currently, no proven therapies for atrophic disease are available, but several agents are being investigated in clinical trials. Future progress is likely to be from improved efforts in prevention and risk-factor modification, personalised medicine targeting specific pathways, newer anti-vascular endothelial growth factor agents or other agents, and regenerative therapies.